Diaspora dalam Pandangan Al-Qur’an (Telaah QS. At-Taubah ayat 122) - Nadia Azkiya; Eka Mulyo Yunus; Risda Alfi Fat Hanna; Halimatussa’diyah Halimatussa’diyah; Saldan Manufa (Jurnal Riset Agama, 2022)
This study aims to determine the diaspora in the view of the Al-Qur’an (Study of the Al-Qur’an Surah At-Taubah verse 122). This study uses a qualitative approach through the method of tahlili interpretation (analysis). The results and discussion of this study indicate that there is a view of the Al-Qur’an on diaspora for the achievement of national education development. This study concludes that good human resources and education can be realized by superior people. Diaspora is believed to have superior potential so that it can play a role in the process of achieving national education development by sharing and conveying the knowledge that has been obtained. This study recommends academics and researchers to develop further related to this research, to find out diaspora in the view of the Al-Qur’an (Study of the Al-Qur’an Surah At-Taubah verse 122).